2008
DOI: 10.1007/s00423-008-0296-4
|View full text |Cite
|
Sign up to set email alerts
|

Liver metastasis as an initial recurrence has no impact on the survival of patients with resectable pancreatic adenocarcinoma

Abstract: We concluded potentially supporting the hypothesis that even patients thought to be at higher risk of liver metastasis may still be given the chance of resection, considering the satisfying survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 33 publications
(49 reference statements)
1
18
0
Order By: Relevance
“…9 Moreover, associations observed in earlier studies vary considerably, possibly due to limited sample size and length of follow-up. For instance, van den Broeck et al 6 found no association between recurrence location and survival, while Tani et al 17 found similar median OS for patients with and without initial liver metastases. However, other studies did find significant correlations between patterns of recurrence and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, associations observed in earlier studies vary considerably, possibly due to limited sample size and length of follow-up. For instance, van den Broeck et al 6 found no association between recurrence location and survival, while Tani et al 17 found similar median OS for patients with and without initial liver metastases. However, other studies did find significant correlations between patterns of recurrence and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [17] reported that the presence of ascites, along with low serum levels of choline esterase and an age >65 years, resulted in an extremely poor prognosis in advanced pancreatic cancer even after palliative chemotherapy. Tani et al [18] demonstrated that if the first recurrence of the disease was liver metastasis, it had no impact on the median survival duration in patients who had undergone curative surgery. However, their study was confined to recurring disease.…”
Section: Discussionmentioning
confidence: 99%
“…PA usually metastasizes to regional nodes, liver, adjacent organs and lungs [114,123] and the incidence of brain metastases is extremely low. Thus, even when patients have metastatic tumors in the brain, the majority of them may die from primary lesions before exhibiting neurologic signs, which may result in the low reported incidence of the metastatic brain tumors from pancreatic cancer [124].…”
Section: Metastases Treatmentmentioning
confidence: 99%